Rhodomela (Rhodophyta, Ceramiales) in the North Atlantic: preliminary results of a molecular investigation. - Sciuto K.; Wolf M. A.; Moro I.; Maggs C. A. (Società Botanica Italiana (SBI), 2011)
Molecular analyses were carried out on different Rhodomela specimens to survey how many species of this genus are present in the North Atlantic.